EFFORTS TO IMPROVE STUDENT'S READING ABILITY BY USING IMAGE STORY MEDIA IN INDONESIAN LESSON - Ti Sara (SENSEI RESEARCH CENTER, 2021)
The objectives of this study were: to determine whether pictorial story media in Indonesian subjects could improve the reading skills of fourth grade students of SD Negeri Pante Ceuremen. This research approach uses qualitative. Type pThis research is Classroom Action Research (PTK). When this research was conducted in August 2018. The subjects in this study areIV SDPante Ceuremen's country districts Pante Ceuremen West Aceh District as much 23 people consisting of 14 men and 9 women. Data collection techniques: tests, observation and documentation. The research instruments were test sheets, observation sheets and documentation sheets. Data analysis techniques aredataincreasing students' reading skills and statistical data for hypothesis testing. From the results of the study it was found that students' reading skills could be improved through pictorial story media in grade IV SD Negeri Pante Ceuremen in the 2018/2019 academic year. Based on the test in the initial conditions, it was found that 20 students scored less than 65. Only 3 students scored above 65. The average score for class 50 with a classification level of completeness was 13%. Based on the results of the Indonesian test on the beauty and cleanliness of the school environment, the reading ability in the first cycle, it was known that the class average was 1480, there were 13 students who had not completed because they got a score of 60 and there were 10 students who got a score of 70. Classical completeness was 43%. Based on the results of the second cycle test shows that the average value of the Indonesian language on the beauty and cleanliness of the school environment increases reading skills by 73.47. Classical completeness is 9.3%. Based on these results, it can be seen that the classical has been completed in cycle II